Green tea [Camellia sinensis (L.) Kuntze] leaves extract and hibiscus (Hibiscus tilliaceus L.) leaves extract as topical hair growth promoter in microemulsion - Amin, Juheini; Djajadisastra, Joshita; Syafhan, Nadia Farhanah; Simamora, Esther Lamria Purba; Wulandari, Kurniati (Agriculture and Natural Resources, 2019)
Green tea [Camellia sinensis (L.) Kuntze] leaves and Hibiscus tilliaceus leaves have been used empirically for hair treatment. However, scientific evidence of their use in herbal preparations for treating hair loss is still limited. This study investigated the hair growth activity, safety and stability of green tea leaves ethanolic extract (GTE) and hibiscus leaves ethanolic extract (HTE) in topical microemulsion preparations. Varied concentrations of each GTE and HTE formulation (2.5%, 5% and 7.5%) were evaluated. The activity of hair growth was investigated using an in vivo method on rats; hair lengths were measured on days 7, 14 and 21 and hair weight on day 21. A safety test was carried out using the upper hand area on 18 volunteers. Physical stability testing involved cycling test along with storage at high temperature (40 ± 2°C), room temperature (25 ± 2°C), and low temperature (4 ± 2°C). The formulated GTE and HTE was successful in producing significant hair growth activity (p < 0.05) compared to the no treatment and vehicle control groups on days 7, 14 and 21. The optimum formula for GTE was at the concentration of 7.5% and for the HTE microemulsion at 7.5% which showed superior hair growth activity compared to 2.5% minoxidil microemulsion after 21 d. None of the formulas showed irritation and all were stable in storage. GTE and HTE microemulsion could be used as potential natural hair growth promoter.